Impact of the 2009 (7th Edition) AJCC Melanoma Staging System in the Classification of Thin Cutaneous Melanomas. (3rd December 2013) - Chu, Vicki H.; Tetzlaff, Michael T.; Torres-Cabala, Carlos A.; Prieto, Victor G.; Bassett, Roland; Gershenwald, Jeffrey E.; McLemore, Michael S.; Ivan, Doina; Wang, Wei-Lien (Billy); Ross, Merrick I.; Curry, Jonathan L.
Abstract : Context . The 7th (2009) edition of the AJCC melanoma staging system incorporates tumor (Breslow) thickness, MR, and ulceration in stratifying T1 primary melanomas. Compared to the prior 6th (2001) edition, MR has replaced CL for thin melanomas. Objective . We sought to identify and report differences of the classification of thin melanomas as well as outcome of SLNB in patients according to the 6th and 7th editions at our institution. Results . 106 patients were identified with thin melanomas verified by wide excision. 31 of 106 thin melanomas were reclassified according to the 7th edition of the AJCC. Of those 31, 15 CL II/III patients (6th edition T1a) were reclassified as T1b based on the presence of mitoses while 16 CL IV patients (6th edition T1b) were categorized as T1a based on the absence of mitoses. 26/31 reclassified patients underwent SLNB, and all were negative. Patients with thin melanoma and a +SLNB (N = 3 ) were all classified as T1b according to both staging systems. Conclusions . In our experience, 29% of thin melanomas were reclassified according to the 7th edition with similar proportions of patients re-distributed as T1a (14%) and T1b (15%). Cases with +SLN corresponded with T1b lesions in both 6th and 7th editions.